2009
DOI: 10.4314/ajbr.v9i2.48778
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl dimethyl bicarboxylate as an effective treatment for chemical-induced fatty liver in rats

Abstract: To assess the protective effect of diphenyl dimethyl bicarboxylate (DDB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…These findings agree with previous results that found that CCl4 treatment significantly increased liver tissue weight, total lipid, TC, TG where CCl4 is induced fatty liver where lipogenesis is produced [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings agree with previous results that found that CCl4 treatment significantly increased liver tissue weight, total lipid, TC, TG where CCl4 is induced fatty liver where lipogenesis is produced [30].…”
Section: Discussionsupporting
confidence: 93%
“…The results related to the deleterious effect of CCl4 itself and its metabolites; CCl4 is metabolized by the cytochrome P-450. CCl4 metabolite trichloromethyl free radicals reacted with protein and lipid within the cell; this reaction accelerated with oxygen and yielded trichloromethyl peroxyl radicals, which attack lipids on the membrane of endoplasmic reticulum faster than trichloromethyl free radical disturbed calcium homeostasis and finally cell death [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…CCl 4 is the most recognized chemical substance used in developing models of liver and kidney damage [5] , [6] . Therefore, CCl 4 -induced liver damage is one of the best ways of inducing damage by xenobiotics and also one of the common methods of screening hepatoprotective or liver treatment drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A significant loss of body weight was observed in the negative control group compared to the control group accompanied with reduced food consumption. An increase in liver weight is common in the case of CCl 4 intoxication due to fatty changes [37].…”
Section: Discussionmentioning
confidence: 99%